The Perception of ChatGPT among Educators: Preliminary Findings - Ogurlu, Uzeyir; Mossholder, Jesse (Research in Social Sciences and Technology- OpenED Network, 2023)
ChatGPT was first released in November 2022, which has led to varying reactions among educators. Educators are one of the major stakeholders in the education system. As a result of this, educators’ perceptions of ChatGPT are worth investigating to inform future policy decision-making. This study examined the perceptions of ChatGPT among educators using an online survey. Thematic coding was conducted to interpret perceptions about their concerns about ChatGPT and their thoughts on the potential benefits of ChatGPT in education. The results indicated that even though educators did not know much about ChatGPT yet, they were open to receiving training about its applicability within education. Educators mentioned plagiarism/cheating, loss of higher-order thinking skills, overreliance on technology, lack of authenticity, decreasing content comprehension, fears of the unknown, and concern for social-emotional well-being as their concerns. On the other hand, educators were hopeful about developing teaching materials to reduce workload, instant information access, and a higher level of teaching using ChatGPT. The findings of the study suggest some important implications and recommendations for educators and policymakers.